I'll do the first problem to get you started.
Part (a)
We have a separable equation. Get the y term to the left side and then integrate to get
![(dy)/(dt) = ky^(1+c)\\\\(dy)/(y^(1+c)) = kdt\\\\\displaystyle \int(dy)/(y^(1+c)) = \int kdt\\\\\displaystyle \int y^(-(1+c))dy = \int kdt\\\\\displaystyle -(1)/(c)y^(-c) = kt+D\\\\\displaystyle -(1)/(c*y^(c)) = kt+D\\\\](https://img.qammunity.org/2021/formulas/mathematics/college/eik10gd8z7zm7b5g3ffii6dj7qbkcig5o5.png)
I'm using D as the integration constant rather than C since lowercase letter c was already taken.
Let's use initial condition that
. This means we'll plug in t = 0 and
. After doing so, solve for D
![\displaystyle -(1)/(c*y^(c)) = kt+D\\\\\displaystyle -(1)/(c*(y_0)^(c)) = k*0+D\\\\\displaystyle D = -(1)/(c*(y_0)^(c))\\\\](https://img.qammunity.org/2021/formulas/mathematics/college/z5a9y7fkyww7xtug3adb82ttlfc6kk3jaq.png)
Let's plug that in and isolate y
![\diplaystyle -(1)/(c)y^(-c) = kt+D\\\\\\\diplaystyle -(1)/(c)y^(-c) = kt-(1)/(c*(y_0)^(c))\\\\\\\diplaystyle y^(-c) = -ckt+(1)/((y_0)^(c))\\\\\\\diplaystyle y^(-c) = (1-c*(y_0)^(c)kt)/((y_0)^(c))\\\\\\\diplaystyle (1)/(y^(c)) = (1-c*(y_0)^(c)kt)/((y_0)^(c))\\\\\\\diplaystyle y^(c) = ((y_0)^(c))/(1-c*(y_0)^(c)kt)\\\\\\\diplaystyle y = \left(((y_0)^(c))/(1-c*(y_0)^(c)kt)\right)^(1/c)\\\\\\\diplaystyle y = (y_0)/(\left(1-c*(y_0)^(c)kt\right)^(1/c))\\\\\\](https://img.qammunity.org/2021/formulas/mathematics/college/ev9pag2e749d5gzxe9f3ipcdbrvbsfo9ob.png)
-------------------------
We end up with
as our final solution. There are likely other forms to express this equation.
========================================================
Part (b)
We want y(t) to approach positive infinity.
Based on the solution in part (a), this will happen when the denominator approaches 0 from the left.
So
as
in which we can effectively "solve" for t showing that
![t \to (1)/(c*(y_0)^(c)k)](https://img.qammunity.org/2021/formulas/mathematics/college/6dus4nemd3iikn2ep89n1zu34zj6f1w969.png)
If we define
, then approaching T from the left side will have y(t) approach positive infinity.
This uppercase T value is doomsday. This the time value lowercase t approaches from the left when the population y(t) explodes to positive infinity.
Effectively t = T is the vertical asymptote.
========================================================
Part (c)
We're told that the initial condition is y(0) = 5 since at time 0, we have 5 rabbits. This means
![y_0 = 5](https://img.qammunity.org/2021/formulas/mathematics/college/4np87alr1aohgi24wff9d13riofyete8vn.png)
Another fact we know is that y(3) = 35 because after three months, there are 35 rabbits.
Lastly, we know that c = 0.01 since the exponent of dy/dt = ky^(1.01) is 1.01; so we solve 1+c = 1.01 to get c = 0.01
We'll use y(3) = 35, c = 0.01 and
to solve for k
Doing so leads to the following:
![\displaystyle y(t) = (y_0)/(\left(1-c*(y_0)^(c)kt\right)^(1/c))\\\\\\\displaystyle y(3) = (5)/(\left(1-0.01*(5)^(0.01)k*3\right)^(1/0.01))\\\\\\\displaystyle 35 \approx (5)/(\left(1-0.0304867k\right)^(100))\\\\\\\displaystyle 35\left(1-0.0304867k\right)^(100) \approx 5\\\\\\\displaystyle \left(1-0.0304867k\right)^(100) \approx (1)/(7)\\\\\\](https://img.qammunity.org/2021/formulas/mathematics/college/qolwaensr3j6jxgb1ysg58r8jvajsx6tz8.png)
![\displaystyle \left(1-0.0304867k\right)^(100) \approx 7^(-1)\\\\\\\displaystyle 1-0.0304867k \approx \left(7^(-1)\right)^(1/100)\\\\\\\displaystyle 1-0.0304867k \approx 7^(-0.01)\\\\\\\displaystyle k \approx (7^(-0.01)-1)/(-0.0304867)\\\\\\\displaystyle k \approx 0.63211155281122\\\\\\\displaystyle k \approx 0.632112\\\\\\](https://img.qammunity.org/2021/formulas/mathematics/college/7sdslyftn11jgvka6fwz7mi2dtructaas8.png)
We can now compute the doomsday time value
![T = (1)/(c*(y_0)^c*k)\\\\\\T \approx (1)/(0.01*(5)^(0.01)*0.632112)\\\\\\T \approx (1)/(0.00642367758836)\\\\\\T \approx 155.674064621806\\\\\\T \approx 155.67\\\\\\](https://img.qammunity.org/2021/formulas/mathematics/college/m7kjouiqg3nosn3u4jni44dtuv3p6cnns8.png)
The answer is approximately 155.67 months